Effects of Euseius stipulatus on establishment and efficacy in spider mite suppression of Neoseiulus californicus and Phytoseiulus persimilis in clementine - Abad-Moyano, Raquel; Urbaneja, Alberto; Hoffmann, D.; Schausberger, Peter (2017)
The two-spotted spider mite, Tetranychus urticae, is one of the most problematic phytophagous pests in Spanish clementine orchards. The most abundant predatory mites in this ecosystem are Euseius stipulatus, Phytoseiulus persimilis and Neoseiulus californicus. Euseius stipulatus is dominant but poorly adapted to utilize T. urticae as prey. It mainly persists on pollen and citrus red mite, Panonychus citri. A recent study suggested that the more efficacious T. urticae predators P. persimilis and N. californicus are negatively affected by lethal and non-lethal intraguild interactions with E. stipulatus. Here, we investigated the potential of N. californicus and P. persimilis to colonize and thrive on young clementine trees infested by T. urticae in presence and absence of E. stipulatus. Presence of E. stipulatus interfered with establishment and abundance of P. persimilis and negatively affected the efficacy of N. californicus in T. urticae suppression. In contrast, the abundance of E. stipulatus was not affected by introduction of a second predator. Trait-mediated effects of E. stipulatus changing P. persimilis and N. californicus behavior and/or life history were the most likely explanations for these outcomes. We conclude that superiority of E. stipulatus in intraguild interactions may indeed contribute to the currently observed predator species composition and abundance, rendering natural control of T. urticae in Spanish clementine orchards unsatisfactory. Nonetheless, stronger reduction of T. urticae and/or plant damage in the predator combination treatments as compared to E. stipulatus alone indicates the possibility to improve T. urticae control via repeated releases of N. californicus and/or P. persimilis.